THE INFLUENCE OF MOBILE BANKING SERVICE QUALITY ON CUSTOMER SATISFACTION (Survey at Customer of PT. Bank Rakyat Indonesia Tbk. Jombang Branch) - Miftakhul Dwi Saputro; Endang Siti Astuti; Devi Farah Azizah (Fakultas Ilmu Administrasi Universitas Brawijaya, 2016)
Penelitian ini bertujuan untuk menjelaskan pengaruh secara parsial dan simultan antara kualitas layanan mobile banking (reliability and responsiveness, assurance and security, convenience, efficiency, easiness to operate) terhadap customer satisfaction. Penelitian ini menggunakan pendekatan kuantitatif dengan jenis penelitian penjelasan. Analisa data dalam penelitian ini menggunakan tahapan analisis deskriptif, uji asumsi klasik, analisis regresi linier berganda dan uji hipotesis. Hasil penelitian menunjukkan bahwa terdapat pengaruh positif dan signifikan secara parsial variabel reliability and responsiveness, assurance and security, convenience), efficiency terhadap customer satisfaction. Selanjutnya terdapat pengaruh positif namun tidak signifikan antara variabel easiness to operate terhadap customer satisfaction. Kemudian terdapat pengaruh positif dan signifikan secara simultan variabel reliability and responsiveness, assurance and security, convenience, efficiency, easiness to operate terhadap customer satisfaction sebesar 83%. Kata Kunci: Reliability and Responsiveness, Assurance and Security, Convenience, Efficiency, Easiness to Operate. ABSTRACT This research objectives are to explain the partial and simultaneous influence between mobile banking service quality (reliability and responsiveness, assurance and security, convenience, efficiency, easiness to operate) on customer satisfaction. This research uses a quantitative approach with the descriptive reseach type. Analysis of the data in this research using the stages of descriptive analysis, classical assumption test, multiple linear regression analysis and hypothesis testing. The research result show if there is partially positive and significant influence reliability and responsiveness, assurance and security, convenience, efficiency on customer satisfaction. Furthermore, there is positive but not significant influence between easiness to operate variable on customer satisfaction. Then there is simultaneously positive and significant influence reliability and responsiveness, assurance and security, convenience, efficiency, easiness to operate variables on customer satisfaction amounted to 83%. Keywords: Reliability and Responsiveness, Assurance and Security, Convenience, Efficiency, Easiness to Operate.